Nexus between Impact Investing and Green Finance in Driving Sustainable Development - Jaya, Oki Setiawan (Advances in Applied Accounting Research, 2024)
Purpose: This study examines the intersection of impact investing and green finance, focusing on their contributions to sustainable development and their impact on reshaping financial markets. Research Design and Methodology: This study employs a qualitative approach to conduct a systematic literature review, analyzing how institutional investors incorporate environmental, social, and governance (ESG) factors into their investment strategies. Findings and Discussion: The research highlights a shift towards sustainability among institutional investors, moving beyond traditional financial-only returns. Key regulations, such as the EU’s SFDR and the TCFD recommendations, support transparency, driving the adoption of sustainable practices. A positive link between robust ESG performance and financial returns illustrates the compatibility of environmental responsibility with profit objectives. Implications: The findings underscore the importance of integrating sustainability into investment decisions to promote a resilient and equitable economic future. It suggests that continued policy support is essential to encourage private investment in sustainable projects, advocating for systemic changes across financial markets to embrace sustainable and inclusive growth.